1999
DOI: 10.1177/0957926599010003004
|View full text |Cite
|
Sign up to set email alerts
|

Genocide or a Failure to Gel? Racism, History and Nationalism in Australian Talk

Abstract: In a context of wide media attention to public debates about the social, political and epistemic entitlements of different groups within Australian society, an understanding of the rhetorical resources and the discursive work doen by differing constructions of `race', has become an important local issue. This article examines data from discussions between two groups of (non-indigenous) university students on a range of contemporary issues concerning race relations in Australia. Participants drew on four common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
127
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(132 citation statements)
references
References 26 publications
4
127
0
1
Order By: Relevance
“…By using these contrast structures, speakers persuasively achieved distancing from the injustices of the past, and therefore undermined the legitimacy of the view that their current practice may be controlling in any way. This was similarly observed in Augoustinos et al's (1999) study on racist talk, where participants distanced themselves from accusations of overt racism by using distanced footing and attributing racism primarily to the older generations.…”
supporting
confidence: 53%
“…By using these contrast structures, speakers persuasively achieved distancing from the injustices of the past, and therefore undermined the legitimacy of the view that their current practice may be controlling in any way. This was similarly observed in Augoustinos et al's (1999) study on racist talk, where participants distanced themselves from accusations of overt racism by using distanced footing and attributing racism primarily to the older generations.…”
supporting
confidence: 53%
“…Martha Augoustinos, Keith Tuffin, and Mark Rapley, for example, have sought to identify patterns of talk and rhetoric in discussions of race relations in Australia (Augoustinos et al 1999). They recorded and anaylzed conversations among two groups of non-indigenous university students on issues pertaining to race relations in Australia, and found that the students' discourse displayed features of what has been characterized as "modem racism".…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some researchers (e.g. [17,18]) have overcome the problem of controlling the one-to-one interview by setting up group discussions, usually in small groups. However, this could cause other ethics-related problems; for example, one member of the group may not practice confidentiality or may show lack of respect to the other participants.…”
Section: Qualitative and Quantitative Aspects Of Research In Educatiomentioning
confidence: 99%